High-performance lead-acid storage battery AGM (Absorbed Glass Mat) separator and preparation method and application thereof
By using specific proportions of glass fiber and two-component organic fibers, the structure of the AGM partition is optimized, and the shortcomings of traditional partitions in electrolyte corrosion and mechanical properties are solved, and higher chemical stability and mechanical properties are achieved, and the fast charging and discharge requirements of modern high-performance batteries are met.
Patent Information
- Application Number
- CN202411901108.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The AGM separators of traditional lead-acid batteries have shortcomings in resisting electrolyte corrosion and mechanical properties, resulting in poor structural stability, short service life and low charge and discharge efficiency, which cannot meet the requirements of modern high-performance batteries for fast charge and discharge.
Using materials such as 25-30° SR glass fiber, 30-35° SR glass fiber, 40-45° SR glass fiber, 14-24° SR centrifugal cotton, two-component organic fibers and vapor phase silica, the high porosity and optimized pore structure are formed through the beating and molding process, which enhances the chemical stability and mechanical properties of the partition.
It significantly improves the chemical stability and mechanical properties of the AGM partition, extends the service life of the battery, improves the charging and discharging efficiency, meets the needs of fast charging and discharging, and enhances the durability and reliability of the battery.
Smart Images

Figure CN119864591A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid battery separator manufacturing, in particular to a high-performance lead-acid battery AGM separator and a preparation method and application thereof. Background Art
[0002] In the field of lead-acid batteries, the performance of AGM separators has a significant impact on the overall performance of the battery. Traditional lead-acid battery AGM separators have many problems in practical applications.
[0003] On the one hand, the materials and structures of traditional AGM separators make them limited in their ability to resist electrolyte corrosion. In the complex and corrosive chemical environment of lead-acid batteries, AGM separators are susceptible to corrosion by electrolytes and have poor long-term stability, which can damage the AGM separator structure, affect the normal operation of the battery, and reduce the battery's service life. On the other hand, traditional AGM separators are deficient in mechanical properties. Under the extrusion during battery assembly and the impact of external forces such as collision and vibration during use, AGM separators are prone to cracking or deformation. This not only affects the stability of the internal structure of the battery, but may also cause battery failure and reduce the safety and reliability of the battery. In addition, the pore structure of traditional AGM separators is often not ideal, the electrolyte storage space is limited, and the ion conduction channel is not smooth enough. This makes the electrolyte unevenly distributed in the AGM separator, the ion transmission efficiency is low, and the battery's charge and discharge efficiency is limited, which cannot meet the requirements of modern high-performance batteries for fast charge and discharge.
[0004] In some application scenarios that require high battery performance, such as electric vehicles and communication base station backup power supplies, the battery needs to be charged and discharged frequently, and must work stably under complex working conditions (such as vibration, temperature changes, etc.). These performance defects of traditional AGM separators seriously affect the performance and reliability of batteries in these scenarios, resulting in reduced battery life and unstable backup power supply. Therefore, there is an urgent need for a high-performance lead-acid battery AGM separator that can overcome the above problems to improve the performance, stability and durability of the battery under complex working conditions and meet the urgent needs of practical applications.
[0005] In view of this, a high-performance lead-acid battery AGM separator and a preparation method and application thereof are provided to overcome the above-mentioned problems. Summary of the invention
[0006] The object of the present invention is to provide a high-performance lead-acid battery AGM separator and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the present invention provides a high-performance lead-acid battery AGM separator, which is composed of 25-30°SR glass fiber (SR is Sjoerdt, the beating degree is calculated according to the drainage time, and the measurement range is 0-100 SR, the same below), 30-35°SR glass fiber and two-component organic fiber, and 40-45°SR glass fiber and 14-24°SR centrifugal cotton, additive fumed silica, etc., wherein the 25-30°SR glass fiber accounts for 40%-50% of the total fiber mass, the 30-35°SR glass fiber accounts for 30%-40% of the total fiber mass, the 40-45°SR glass fiber accounts for 5%-10% of the total fiber mass, the 14-24°SR centrifugal cotton accounts for 3%-8% of the total fiber mass, the additive fumed silica, etc. accounts for 1%-3% of the total fiber mass, and the two-component organic fiber accounts for 3%-18% of the total fiber mass. The two-component organic fiber is a combination of polyester fiber and polyacrylonitrile fiber, and the two cooperate with each other to form a synergistic effect.
[0008] Furthermore, 30-35° SR glass fibers are combined with 25-30° SR glass fibers to form a diversified pore structure.
[0009] Furthermore, the bicomponent organic fibers composed of polyester fibers and polyacrylonitrile fibers form an interpenetrating network structure through a synergistic effect.
[0010] Furthermore, the porosity of the AGM separator is not less than 92%, and the liquid absorption rate is not less than 4.8 g / m².
[0011] A method for preparing a high-performance lead-acid battery AGM separator comprises the following steps: Beating process: Use a beater, add sulfuric acid solution to adjust the pH value of the beating environment; weigh glass fiber and two-component organic fiber in proportion, slowly add them to the beater, add additives during the beating process, the added additives include but are not limited to fumed silica, the fumed silica used to prevent the fibers from sticking to each other and agglomerating during the beating process, thereby improving the stability of the separator structure, corrosion resistance, and reducing the internal short-circuit failure rate of the battery accounts for 1%-3% of the total fiber mass, and beat at a speed of 1500 rpm for 60 minutes; Add water for mixing and subsequent treatment: Stir for 30 minutes when the beating is carried out for 30 minutes; pour the fiber slurry into a special mold, apply 5MPa pressure to form it, and dry it at 80℃ for 24 hours; cut the dried AGM separator according to the cutting accuracy of ±0.5mm, and conduct appearance inspection and physical property test.
[0012] Furthermore, the pH value of the pulping environment is controlled at 3.5.
[0013] Furthermore, during the water adding and mixing process, the deionized water was 5 times the total fiber mass, and then stirred at 1000 rpm.
[0014] The application of a high-performance lead-acid battery AGM separator, used in electric vehicle batteries and communication base station backup power supplies, can significantly improve the performance and durability of the battery under frequent charging and discharging, temperature changes and complex working conditions, and ensure stable power supply.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In terms of chemical stability, the specific proportion of 25-30°SR glass fiber in this high-performance lead-acid battery AGM separator enables the separator to resist electrolyte corrosion, extend its life, overcome the problem of poor stability of traditional separators, and enhance battery durability and reliability.
[0016] 2. In terms of mechanical properties, a variety of fibers are reasonably matched, including two-component organic fibers that form an interpenetrating network structure, which gives the separator high strength and toughness, disperses and absorbs external stress, ensures the stability of the battery structure, and avoids short-circuit failures; the 40-45° SR glass fiber woven network can buffer the stress changes of the plate and reduce separator damage and performance degradation.
[0017] 3. The optimization of pore structure is reflected in the interweaving of 25-30°SR and 30-35°SR glass fibers in a specific ratio to construct diversified pores, which is beneficial to electrolyte storage and ion transmission, improves charging and discharging efficiency, and meets the needs of fast charging and discharging; 40-45°SR glass fibers can also refine pores, block the migration of active substances, and improve safety and stability.
[0018] 4. Fumed silica has a high specific surface area and good dispersibility. It can be adsorbed on the fiber surface and play a role similar to "isolation" and "lubrication", making it less likely for the fibers to stick to each other or agglomerate during the pulping process. It can significantly improve the structural integrity retention rate of the separator, enhance the tensile and compressive strength, extend the battery cycle life, effectively slow down the erosion of the separator by the electrolyte, reduce the corrosion rate, reduce corrosion pits and fiber breakage, reduce the internal short-circuit failure rate of the battery caused by separator corrosion, ensure the stability of the separator performance, improve the reliability and service life of the battery, and make the battery perform better in different application scenarios.
[0019] 5. In terms of application performance, in electric vehicle batteries, its high porosity, high liquid absorption rate and excellent mechanical properties ensure the supply of electrolyte and ion transmission, extend the cycle life, reduce endurance attenuation, and improve the use efficiency and economy; in the backup power supply of communication base stations, high stability and long cycle life can provide stable power supply in the event of a city power failure with little performance degradation. It relies on the fiber synergy effect to ensure normal operation, overcomes problems such as unstable power supply of traditional separators, improves reliability and stability, ensures the operation of communication networks, reduces failures, and has a positive role in promoting the development of the lead-acid battery field. It comprehensively solves the problems of traditional AGM separators, improves the performance, stability and durability of batteries under complex working conditions, and meets actual application needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a schematic diagram of a high-performance lead-acid battery AGM separator and its preparation method and application. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] See also Figure 1 , the present invention provides a technical solution: Embodiment 1
[0023] Material composition and structural synergy benefits: Fiber components are multi-functional and synergistic: 25-30°SR glass fiber and 30-35°SR glass fiber are not only compatible with each other in proportion (accounting for 45% and 35% of the total fiber mass, respectively, within their respective reasonable ranges of 40%-50% and 30%-40%), but also their chemical stability and mechanical strength properties complement each other. The former shows a structural integrity retention rate of up to 98.5% in highly corrosive electrolytes, laying the foundation for the corrosion resistance and structural stability of the overall separator; the latter focuses on constructing a diversified pore structure (porosity of 48% and pore size of 0.8-45 microns), and the two work together to ensure the performance balance of the separator under different working conditions. For example, under long-term high-load charging and discharging and impurity fluctuations in the electrolyte, this combination can effectively prevent the separator from failing due to corrosion or structural deformation, extending the battery cycle life by 32%, which is significantly better than ordinary separators.
[0024] The polyester fiber and polyacrylonitrile fiber in the two-component organic fiber are composed of a ratio of 50%:50% (10% of the total fiber mass is also in the reasonable range of 3%-18%), forming an interpenetrating network structure through synergistic effect. The 4.5MPa tensile strength and 28% elongation at break provided by the polyester fiber ensure the mechanical integrity of the separator, and there is no rupture or deformation after 120 times of 22g acceleration impact; the polyacrylonitrile fiber has an adsorption rate of up to 96% for the electrolyte and controls the electrolyte concentration deviation within ±2.5%, which optimizes the ion transmission environment, improves the battery charging and discharging performance, and increases the power conversion efficiency by 15%. After 1200 temperature cycle tests (-15℃-65℃), the integrity and stability of the separator remain good, effectively adapting to the needs of the battery at different operating temperatures and reducing performance fluctuations caused by temperature changes.
[0025] 40-45°SR glass fiber accounts for 7% of the total fiber mass (within the range of 5%-10%), and its high strength (tensile strength of 5.2MPa, compressive strength of 4.0MPa) is matched with the high toughness and good adsorption performance of 14-24°SR centrifugal cotton (accounting for 3% of the total fiber mass, in the range of 3%-8%). In the simulation test of the expansion and contraction of the positive and negative plates of the battery, the glass fiber was subjected to 120 times of 6% volume change stress, and the separator did not break or deform. The pore structure was optimized, and the pore uniformity was improved by 48%, effectively blocking the migration of active substances in the positive and negative plates, and the migration rate was reduced by 85%; after the centrifugal cotton was subjected to 250 times of 18g acceleration impact test, the separator toughness remained good, there was no structural damage, and the amount of electrolyte adsorbed could reach 8.5 times its own mass. The synergistic effect of the two ensures the structural stability of the separator and the rational distribution of the electrolyte under different environmental conditions, increasing the battery's low-temperature (-12°C) capacity retention rate by 22% and high-temperature (55°C) capacity retention rate by 18%, broadening the battery's applicable temperature range to -32°C-68°C.
[0026] Structural properties associated benefits: The diversified pore structure (porosity 48% and pore size 0.8-45 microns) formed by the combination of 30-35°SR glass fiber and 25-30°SR glass fiber provides sufficient and suitable storage space for the electrolyte, ensuring that the electrolyte can fully infiltrate every corner of the separator during the entire cycle of battery charge and discharge, so that ion transmission always has a stable and good dielectric environment. At the same time, this diversified pore structure significantly reduces the resistance to ion transmission in the separator, increases the ion migration rate by 55%, and improves the battery charge and discharge efficiency by 22%. In high-rate charge and discharge scenarios, such as the fast charging needs of electric vehicles, this structure can effectively reduce the charging time (28% shorter than ordinary separators) and provide stronger and more lasting power output during discharge (discharge power output increased by 20%).
[0027] The interpenetrating network structure formed by the synergistic effect of the two-component organic fiber composed of polyester fiber and polyacrylonitrile fiber enhances the integrity and stability of the separator. In the simulated battery transportation collision and use vibration test, after 120 times of 22g acceleration impact, the separator did not break or deform, which effectively ensured the integrity and stability of the internal structure of the battery, ensured that the battery can continue to operate normally, reduced the risk of battery failure caused by separator damage, and improved the reliability of the battery system.
[0028] Performance parameter advantages: The porosity of the AGM separator is as high as 93% (not less than 92%), and the liquid absorption rate reaches 5.0g / m² (not less than 4.8g / m²). The high porosity means that there is a large amount of space inside the separator for electrolyte storage and ion transmission, like a spacious highway network, providing a convenient channel for the flow of electrolyte and the migration of ions, greatly improving the charging and discharging efficiency of the battery. The high liquid absorption rate indicates that the separator has a strong adsorption capacity for electrolyte, like an efficient sponge, which can quickly and massively absorb and store electrolyte, ensuring that during the operation of the battery, even under complex working conditions, such as acceleration, deceleration, and turning of electric vehicles, the electrolyte can be stably distributed in the separator, providing a stable environment for ion transmission, thereby improving the overall performance of the battery. For example, when electric vehicles accelerate or decelerate suddenly, the electrolyte distribution stability is improved by 38%, effectively avoiding problems such as local overheating or insufficient reaction caused by uneven electrolyte distribution, and ensuring the consistency and stability of battery performance.
[0029] Key role of preparation method: Optimization of pulping process: Use a pulper and add sulfuric acid solution to adjust the pulping pH to 3.5. At this pH value, the hydrolysis reaction on the fiber surface increases the roughness by 65%, the friction is increased, and it is beneficial to the dispersion of the fibers. Add fibers in proportion and add fumed silica accounting for 2% of the total fiber mass during the pulping. Add fibers slowly to prevent accumulation, and fumed silica adsorbs on the fiber surface. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates is reduced from about 150.23 microns to about 60.15 microns, a decrease of 60.0%; the standard deviation of fiber distribution per unit area is reduced from about 35.42 to 21.25, and the uniformity is improved by about 40.0%. After 60 minutes of pulping, the fibers form a uniform network structure to ensure the uniformity of the porosity of the AGM separator. The deviation is reduced from ±15.32% to within ±9.85%, an increase of about 35.7%. This uniform structure is the basis for ensuring the good performance of the AGM separator. If the porosity can be made more uniform, the storage and ion conduction of the electrolyte can be improved, and the battery's charge and discharge efficiency can be improved. In the battery charge and discharge efficiency test, the lead-acid batteries with the same specifications but with and without the AGM separators added with fumed silica were compared. Under the 1C rate charge and discharge conditions, the battery with fumed silica added had a charge and discharge efficiency that increased from 80.12% to about 92.35%, and the increase was accurately calculated to be 15.3%.
[0030] Precise control of water mixing and subsequent treatment: After beating for 30 minutes, slowly add deionized water 5 times the total fiber mass. Use water as a diluent and lubricant, stir at 1000 rpm for 30 minutes to evenly disperse the fibers in the water into a stable slurry. Pour into the mold and apply 5MPa pressure to form, the fibers are tightly interwoven and the pore structure is fixed. Dry at 80℃ for 24 hours, and the water evaporation rate is 0.48g / h, which not only maintains the structure but also improves efficiency. The cutting accuracy is controlled at ±0.5mm, and the appearance and physical properties are tested after cutting to ensure that there is no damage, the holes are uniform and the performance meets the standards. The precise water addition, mixing and subsequent processing steps ensure the physical structure integrity and performance consistency of the separator, avoid the degradation of the separator performance due to defects in the processing process, and provide a reliable foundation for the high-performance operation of the battery.
[0031] Application field performance: Advantages of electric vehicle battery applications: In electric vehicle batteries, due to its high porosity, high liquid absorption rate and excellent mechanical properties, it can ensure a stable supply of electrolyte and smooth transmission of ions under frequent charging and discharging and complex vibration environments. Its cycle life is 32% longer than that of ordinary separators, which effectively reduces the frequency of battery replacement and reduces the cost of use. The range attenuation rate is reduced by 22%. In the daily use of electric vehicles, whether it is frequent starting and stopping on urban roads or long-term driving on highways, the AGM separator can ensure the stability of battery performance and improve the efficiency and economy of electric vehicles. For example, on a long-distance trip, electric vehicles using this AGM separator have less fluctuation in range than vehicles using ordinary separators, can plan trips more accurately, and reduce additional charging time and costs caused by range anxiety.
[0032] Benefits of backup power supply for communication base stations: In the backup power supply of communication base stations, its high stability and long cycle life can ensure that the battery can quickly and stably power the communication equipment when the mains fails, and the performance degradation is minimal during long-term standby. The power supply response time is shortened by 18% when the mains fails, which can ensure the normal operation of communication equipment more quickly and reduce the risk of communication interruption caused by power outages. The performance degradation rate of long-term standby (one year) is controlled within 4%, and the battery working stability is improved by 32% when the ambient temperature changes (-18℃-55℃), which effectively reduces the risk of communication failure caused by power problems, ensures the stable operation of communication base stations, and ensures the reliability and continuity of communication networks. Under extreme weather conditions, such as hot summer or cold winter, the AGM separator can keep the battery in good performance and provide continuous and stable power support for communication base stations.
[0033] In terms of the stability of the partition structure, the structural integrity of the partition is monitored in real time and accurately in the accelerated aging experiment simulating the battery cycle charge and discharge process. After 500 cycles, the proportion of obvious structural deformation and local damage detected by X-ray fluoroscopy and image analysis technology for the partition without adding fumed silica was about 30.15%. Under the same experimental conditions, this proportion was only about 5.23% for the partition with added fumed silica (addition amount was 4%), and the structural integrity retention rate was increased by 82.7%. Professional material mechanics testing equipment was used to test the tensile strength and compressive strength of the partition. When fumed silica was not added, the tensile strength of the partition was about 1.23MPa on average after multiple measurements, and the compressive strength was about 2.52MPa. After adding fumed silica, the tensile strength increased to 1.64MPa, an increase of 33.3%, and the compressive strength increased to 3.23MPa, an increase of about 28.2%. Based on the improvement of structural stability, in specific application scenarios (such as temperature range of 25℃-40℃, discharge depth of 60%-80%), the average service life of batteries without fumed silica is 400-500 cycles according to statistics of a large number of samples. The average service life of batteries with fumed silica is extended to about 600-800 cycles, which is 50%-60% longer than that of batteries without fumed silica.
[0034] In terms of the corrosion resistance of the separator, in the corrosive environment simulation experiment, the AGM separator was immersed in a highly corrosive solution with a composition similar to that of the lead-acid battery electrolyte (sulfuric acid concentration of 30%-35%, containing a small amount of impurity ions such as iron ions, copper ions, etc., with concentrations of 10ppm-20ppm respectively). The mass loss rate of the separator was accurately measured every 24 hours. The mass loss rate of the separator without adding fumed silica after immersion for 100 hours was about 10.25% on average after multiple measurements. The mass loss rate of the separator with added fumed silica (addition amount of 5%) was only about 6.53%, and the corrosion rate was reduced by 36.3%. After a long-term immersion experiment (500 hours), the microstructure of the separator was carefully observed using a high-resolution scanning electron microscope. The surface of the separator without adding fumed silica was statistically found to have a large number of corrosion pits, about 50-60 per square millimeter, and the fiber breakage phenomenon was serious, and the fiber diameter was reduced by an average of about 20.35%. The surface of the separator with added fumed silica is relatively flat, with only 10-15 corrosion pits per square millimeter, the fiber diameter is reduced by about 12.12% on average, and the fiber structure remains relatively intact. This shows that fumed silica effectively slows down the erosion of the separator by the electrolyte, significantly ensuring the stable performance of the separator during long-term use, greatly reducing the probability of internal short circuits in the battery due to corrosion of the separator, and making the battery's performance less volatile and more reliable throughout its service life. For example, in a batch of 100 groups of comparative test batteries, the incidence of internal short circuit failures due to corrosion of the separator during use of batteries without the addition of fumed silica was about 15%, while the failure rate of batteries with the addition of fumed silica was reduced to less than 5%. Embodiment 2
[0035] Material composition: 25-30°SR glass fiber: 42% of the total fiber mass. Although it has a certain chemical stability, it can maintain a structural integrity of 95% after 1000 hours of immersion test in a highly corrosive electrolyte of a lead-acid battery (sulfuric acid concentration is about 30%-35%, containing trace impurities such as iron ions and copper ions, and the concentration is about 5-15ppm). However, compared with Example 1, its corrosion resistance is weakened when used under long-term high loads. Its tensile strength reaches 3.5MPa. Under extreme working conditions, its support strength for the partition structure is slightly inferior. For example, after withstanding 800 times of 15g acceleration impact, the deformation of the partition structure is about 5%, which is higher than that of Example 1.
[0036] 30-35°SR glass fiber: 38% of the total fiber mass. The pore structure constructed in combination with 25-30°SR glass fiber is relatively good, with a porosity of 46% and a pore size distribution of 1-40 microns, but the diversity is not as good as in Example 1. This results in a reduction in the richness of electrolyte storage space and ion conduction channels. In the battery charge and discharge cycle test, the electrolyte infiltration time is extended by 20%, the ion transmission resistance is increased by 30%, and the battery charge and discharge efficiency is affected to a certain extent. The charging time is extended by 15% compared with Example 1, and the discharge power output is reduced by 12%.
[0037] Bicomponent organic fiber: accounts for 13% of the total fiber mass, of which polyester fiber accounts for 60% and polyacrylonitrile fiber accounts for 40%. Polyester fiber is relatively abundant, with a tensile strength of up to 4.2MPa and an elongation at break of 25%, which makes the partition have good mechanical properties and can withstand a certain degree of external force impact. After 100 times of 20g acceleration impact, the partition has no cracking or deformation. However, polyacrylonitrile fiber is less, and the adsorption rate of electrolyte is 92%, resulting in a decrease in the uniformity of electrolyte adsorption and distribution, poor ion transmission stability, and relatively large voltage fluctuations during battery charging and discharging, with a voltage fluctuation range of about ±5%, while the voltage fluctuation range of Example 1 is within ±2.5%.
[0038] 40-45°SR glass fiber: 6% of the total fiber mass. The strength of the fiber network formed and the optimization effect on the pore structure are not as good as in Example 1. In the simulation test of the expansion and contraction of the positive and negative plates of the battery, after withstanding 100 times of 5% volume change stress, although the separator did not break or deform, the structural deformation amount reached 8%, which is higher than in Example 1. Its improvement in pore uniformity is only 35%, and the mobility of effectively blocking the migration of active substances in the positive and negative plates is reduced to 75%. The short-circuit resistance is also reduced, which increases the risk of internal short circuit in the battery.
[0039] 14-24°SR centrifugal cotton: 1% of the total fiber mass. Although its toughness and adsorption properties can play a certain role, and the amount of electrolyte adsorbed can reach 7 times its own mass, due to its low content, the effect of improving overall durability and ensuring electrolyte supply is not as obvious as in Example 1. Under long-term use or complex working conditions, such as in the temperature cycle (-10℃-60℃) test, after 1000 cycles, the battery performance declines relatively quickly, and the capacity retention rate decreases by 15%, while Example 1 only decreases by 8%.
[0040] Performance parameters: porosity is 92%, and liquid absorption rate is 4.9g / m². The porosity and liquid absorption rate are slightly lower than those in Example 1, which makes the electrolyte storage and ion transmission channels relatively limited. In the ion migration rate test, it is 18% lower than that in Example 1, the battery charge and discharge performance has declined, the cruising range reduction ratio is relatively high, and the cycle life is shortened. In specific application scenarios (such as temperature range 25℃-40℃, discharge depth 60%-80%), the average service life of batteries without adding fumed silica is 400-450 cycles according to a large number of samples, while Example 1 is about 600-800 cycles.
[0041] Preparation method: Beating process: The pH value of the beating environment is adjusted to 3.5, and the fibers are weighed in proportion and slowly added to the beater. During the beating process, fumed silica is added at a rate of 1.5% of the total fiber mass. Due to the low content of fumed silica, the effects on fiber dispersion, mechanical property improvement, electrolyte adsorption distribution optimization, and chemical stability enhancement are not as good as in Example 1. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates decreased from about 120 microns to about 70 microns, a decrease of 41.7%; the standard deviation of fiber distribution per unit area decreased from about 32 to 25, and the uniformity increased by about 21.9%, both lower than in Example 1. The uniformity of the formed fiber dispersion system is slightly poor, resulting in less than ideal structure and performance of the partition after molding.
[0042] Add water for mixing and subsequent treatment: add 5 times the fiber mass of deionized water when beating for 30 minutes, then stir at 1000 rpm for 30 minutes, pour into the mold and form under 5MPa pressure, dry at 80℃ for 24 hours, cut with an accuracy of ±0.5mm and test. The steps are the same as those in Example 1, but due to the difference in fiber raw materials, the final separator performance is not as good as that in Example 1, and the stability and reliability shown in battery applications are relatively low.
[0043] Application areas: Applied to electric vehicle batteries and communication base station backup power supplies. In electric vehicles, the reduction ratio of cruising range is slightly larger than that of embodiment 1, about 25%, and the battery cycle life is slightly shorter. Under complex working conditions such as frequent start-stop or high-speed driving, the battery performance fluctuates significantly. For example, in a 200-kilometer driving test, the battery voltage fluctuates 8 times, while embodiment 1 only fluctuates 3 times. In the communication base station backup power supply, the power supply stability is slightly poor when the mains fails, and the performance degradation ratio of the long-term backup partition is relatively high. During the one-year backup period, the performance degradation rate reaches 8%, which may affect the normal operation of the communication base station during the mains interruption. Embodiment 3
[0044] Material composition: 25-30°SR glass fiber: 48% of the total fiber mass. High chemical stability. In the above-mentioned corrosive electrolyte environment, the structural integrity retention rate reached 99% after 1200 hours of immersion test. However, due to the high content, the fibers are relatively close. This limits the role of other fibers to a certain extent. For example, the formation of the pore structure is not ideal, the electrolyte storage space is relatively reduced, and the adsorption and distribution of the electrolyte by the two-component organic fiber is also hindered to a certain extent, affecting the improvement of the battery charging and discharging efficiency.
[0045] 30-35°SR glass fiber: 32% of the total fiber mass. The pore structure formed in conjunction with 25-30°SR glass fiber is not rich and diverse enough, with a porosity of 45% and a pore size distribution of 2-38 microns, and relatively few ion conduction channels. During the battery charging and discharging process, the ion transmission speed slows down, the charging time is extended by 25%, the discharge depth is limited, the discharge power output is reduced by 15%, and the overall battery performance is reduced.
[0046] Bicomponent organic fiber: 10% of the total fiber mass, of which polyester fiber accounts for 40% and polyacrylonitrile fiber accounts for 60%. The larger amount of polyacrylonitrile fiber makes the electrolyte adsorption distribution better, with an adsorption rate of 97%, but the smaller amount of polyester fiber leads to insufficient mechanical strength of the separator, with a tensile strength of 3.0MPa. During the assembly and use of the battery, there is a risk of rupture or deformation, especially when it is subjected to a large external force impact. For example, after 150 times of 25g acceleration impact, the probability of the separator rupture is 10%, which may cause damage to the internal structure of the battery and affect the normal operation and service life of the battery.
[0047] 40-45°SR glass fiber: 8% of the total fiber mass. It has a certain improvement effect on the strength and pore structure of the separator, with a tensile strength of 4.8MPa and a compressive strength of 3.5MPa. However, due to the uncoordinated overall fiber ratio, its advantages cannot be fully utilized. The effect is limited in enhancing the tensile and compressive resistance and optimizing the penetration and diffusion of the electrolyte. It cannot effectively reduce the risk of internal short circuits in the battery, and has a certain impact on the long-term stability of the battery.
[0048] 14-24°SR centrifugal cotton: 2% of the total fiber mass. Toughness and adsorption performance have limited effect on overall performance improvement. The amount of electrolyte adsorbed is 7.5 times its own mass. It is not as good as Example 1 in ensuring battery durability and electrolyte supply under complex working conditions. In low temperature environment or long-term use, the battery capacity retention rate decreases rapidly. At -10°C, after 800 charge and discharge cycles, the capacity retention rate decreases by 20%, while Example 1 only decreases by 12%.
[0049] Performance parameters: Porosity is 92.5%, and liquid absorption rate is 4.85g / m². The parameters are different from those in Example 1, which affects the effects of electrolyte and ions during battery charging and discharging, resulting in a decrease in the overall performance of the battery. In electric vehicle applications, the cruising range is reduced by a large proportion, about 30%, and the cycle life is shortened; in communication base station backup power supply applications, the power supply stability and long-term backup performance are not as ideal as in Example 1.
[0050] Preparation method: Beating process: adjust the beating pH value to 3.5, weigh the fiber and slowly add it to the beater and add fumed silica (accounting for 2.5% of the total fiber mass), and beat at 1500 rpm for 60 minutes. The slightly higher content of fumed silica helps the fiber dispersion to a certain extent, and the average diameter of the fiber agglomerates is reduced from about 130 microns to about 65 microns, a decrease of 50%, but it may cause the fiber surface to be over-covered, affecting the interaction between the fibers, making the structure of the separator uneven after molding, affecting the porosity and liquid absorption rate, and thus affecting the battery performance.
[0051] Mixing with water and subsequent treatment: add 5 times the fiber mass of deionized water after beating for 30 minutes, then stir at 1000 rpm for 30 minutes, form at 5MPa pressure, dry at 80℃ for 24 hours, cut with an accuracy of ±0.5mm and test. The process is similar to that of Example 1, but due to the ratio of fiber raw materials and additives, the final separator performance is not as good as that of Example 1, and unstable performance is likely to occur during battery use.
[0052] Application areas: It has certain application performance in electric vehicle batteries and communication base station backup power supplies. However, compared with the first embodiment, in electric vehicles, the battery performance is significantly reduced under complex working conditions, such as a large reduction in cruising range and a shortened cycle life; in the communication base station backup power supply, the power supply stability and the ratio of long-term standby performance degradation are not as ideal as in the first embodiment, which may cause insufficient power supply or power interruption of the communication base station when the mains fails, affecting the communication quality and reliability. Embodiment 4
[0053] Material composition: 25-30°SR glass fiber: 40% of the total fiber mass. Good chemical stability, with a structural integrity retention rate of 97% after 1100 hours of immersion test, but slightly weaker in long-term corrosion resistance than Example 1, and may not be sufficient to support the partition structure under extreme working conditions. Its tensile strength is 3.3MPa, and after 700 times of 18g acceleration impact, the partition structure deformation is about 6%.
[0054] 30-35°SR glass fiber: 40% of the total fiber mass. The formed pore structure is better, with a porosity of 47% and a pore size distribution of 1.2-42 microns. However, due to the change in proportion, the synergistic effect with 25-30°SR glass fiber is not as good as in Example 1, which has a certain impact on electrolyte storage and ion conduction efficiency. In the battery charge and discharge cycle test, the electrolyte infiltration time is extended by 18%, and the ion transmission resistance is increased by 28%.
[0055] Bicomponent organic fiber: accounts for 13% of the total fiber mass, of which polyester fiber and polyacrylonitrile fiber each account for half. The mechanical properties and electrolyte adsorption and distribution performance are good. The tensile strength of polyester fiber is 4.0MPa, the elongation at break is 26%, and the electrolyte adsorption rate of polyacrylonitrile fiber is 95%. However, due to the change in the overall fiber ratio, it is not as obvious as Example 1 in improving the integrity and stability of the separator. In the simulated temperature cycle (-12℃-62℃) test, after 1100 cycles, the deformation of the separator structure was 10%, while that of Example 1 was 5%.
[0056] 40-45°SR glass fiber: 5% of the total fiber mass. The fiber network formed has limited effect on the optimization of the strength and pore structure of the separator, with a tensile strength of 4.5MPa and a compressive strength of 3.2MPa. The buffering capacity is insufficient when the battery plate stress changes, and the short-circuit resistance is weak. In the simulation test of the expansion and contraction of the positive and negative plates of the battery, after 110 times of 4% volume change stress, the deformation of the separator structure reached 10%, which is higher than that of Example 1.
[0057] 14-24°SR centrifugal cotton: 2% of the total fiber mass. The toughness and adsorption performance contribute relatively little to the overall performance improvement of the battery. The amount of electrolyte adsorbed is 7.2 times its own mass, and the effect is limited in ensuring battery durability and electrolyte supply under complex working conditions. Under long-term use or complex working conditions, such as in an environment with large humidity changes (30%-90%), after 900 charge and discharge cycles, the battery performance degradation rate reaches 18%, while the first embodiment is 10%.
[0058] Performance parameters: Porosity is 92%, and liquid absorption rate is 4.82g / m². Compared with Example 1, these parameters lead to a decrease in the electrolyte storage and ion transmission effect during the battery charging and discharging process, affecting the overall performance improvement of the battery. In the ion migration rate test, it is 20% lower than that of Example 1, and the battery charging and discharging performance is reduced.
[0059] Preparation method: Beating process: adjust the pH value of the beating environment to 3.5, take the fibers in proportion and slowly add them to the beater, and add fumed silica to 1% of the total fiber mass. The fumed silica content is low, and it has limited effects on fiber dispersion, mechanical property improvement, electrolyte adsorption distribution optimization, and chemical stability enhancement during the fiber beating process. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates decreased from about 140 microns to about 80 microns, a decrease of 42.9%; the standard deviation of fiber distribution per unit area decreased from about 34 to 28, and the uniformity increased by about 17.6%, which could not effectively improve the overall performance of the separator.
[0060] Add water, mix and treat afterwards: add 5 times the mass of fiber deionized water when beating for 30 minutes, then stir at 1000 rpm for 30 minutes, press 5MPa to form, dry at 80℃ for 24 hours, cut with a precision of ±0.5mm and inspect. The steps are the same as those in Example 1, but due to the ratio of fiber raw material and additive, the performance of the final separator is not as good as that in Example 1.
[0061] Application areas: Used in electric vehicle batteries and communication base station backup power supplies. In electric vehicles, battery performance declines significantly under long-term use and complex working conditions. For example, the cruising range is reduced by a large proportion, about 28%, and the cycle life is shortened. In the backup power supply of communication base stations, the power supply stability is poor when the mains fails, and the performance of long-term backup partitions declines rapidly. Within the one-year standby period, the performance degradation rate reaches 10%, affecting the normal operation of communication base station equipment.
[0062] Comparative Example 1: Performance parameters: The lower porosity and liquid absorption rate limit the storage of electrolyte and ion transmission in the separator, making the energy conversion efficiency of the battery low during charging and discharging. In the ion migration rate test, it is 35% lower than that of Example 1, the cruising range is significantly shortened, and the cycle life is greatly reduced. In specific application scenarios (such as temperature range 25℃-40℃, discharge depth 60%-80%), the average service life of the battery without adding fumed silica is only 300-400 cycles according to a large number of sample statistics, which is much lower than the 600-800 cycles of Example 1.
[0063] Preparation method: Beating process: The pH value of the beating environment is 3.5. The fibers are weighed in proportion and slowly added to the beater. During the beating process, 0.5% of the total fiber mass is added with fumed silica. Due to the extremely low content of fumed silica, the fiber dispersion effect is poor and fiber agglomerations are easily formed. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates only decreased from about 180 microns to about 150 microns, a decrease of 16.7%; the standard deviation of fiber distribution per unit area decreased from about 40 to 35, and the uniformity increased by about 12.5%. This results in an uneven separator structure, poor mechanical properties, and uneven adsorption and distribution of the electrolyte, affecting the overall performance of the battery.
[0064] Add water for mixing and subsequent treatment: add 5 times the fiber mass of deionized water when beating for 30 minutes, then stir at 1000 rpm for 30 minutes, pour into the mold and form under 5MPa pressure, dry at 80℃ for 24 hours, cut with an accuracy of ±0.5mm and test. Although the preparation steps are similar to those in Example 1, due to the unreasonable ratio of fiber raw materials and additives, the final separator performance is far inferior to that in Example 1, and cannot meet the normal use requirements in battery applications, and is prone to various failures.
[0065] Application fields: When applied to electric vehicle batteries and communication base station backup power supplies, in electric vehicles, due to poor battery performance, seriously insufficient cruising range, and short cycle life, the battery needs to be replaced frequently, increasing the cost of use. For example, an electric car using the partition in the comparative example may have a cruising range of more than 40% less than the same model using the partition in Example 1, and the battery may need to be replaced after 1-2 years of use, while the partition in Example 1 can support a usage cycle of 3-5 years. In the backup power supply of a communication base station, the power supply is unstable when the mains fails, and it cannot be reliably supplied for a long time, which may cause the communication base station equipment to stop working due to power outages, affecting the normal operation of the communication network. In the case where a mains failure lasts for more than 8 hours, the backup power supply of the communication base station using the partition in the comparative example may experience problems such as power outages or excessive voltage fluctuations that cause the communication equipment to restart, while the partition in Example 1 can provide stable power supply to ensure the normal operation of the communication base station.
[0066] Comparative Example 2: Material composition: 25-30°SR glass fiber: 55% of the total fiber mass. Too much 25-30°SR glass fiber makes the separator too rigid and reduces flexibility, which makes it easy to break when the battery is subjected to external impact or vibration. Although its tensile strength reaches 4.2MPa, its elongation at break is only 18%. After withstanding 100 times of 30g acceleration impact, the probability of the separator breaking is 20%. At the same time, the fibers are closely arranged, the pore structure is limited, the porosity is 44% and the pore size distribution is 4-32 microns, which is not conducive to electrolyte penetration and ion transmission, and reduces the battery charging and discharging efficiency.
[0067] 30-35°SR glass fiber: 25% of the total fiber mass. The pore structure formed by the 25-30°SR glass fiber is not ideal, and it cannot provide sufficient storage space and good ion conduction channels for the electrolyte, resulting in slow ion migration, increased internal resistance and significant heat generation during the battery charge and discharge process, affecting battery performance and service life. In the battery charge and discharge cycle test, the electrolyte infiltration time was extended by 40% and the ion transmission resistance increased by 50%.
[0068] Bicomponent organic fiber: accounts for 15% of the total fiber mass, of which polyester fiber accounts for 30% and polyacrylonitrile fiber accounts for 70%. Although more polyacrylonitrile fiber is conducive to electrolyte adsorption, with an adsorption rate of 98%, too little polyester fiber makes the separator mechanical strength insufficient, with a tensile strength of 2.5MPa, and it is easy to be damaged during battery assembly and use. In addition, the overall fiber ratio is not coordinated, which affects the synergistic effect of the bicomponent organic fiber and reduces the stability and reliability of the separator.
[0069] 40-45°SR glass fiber: 3% of the total fiber mass. Due to insufficient content, it has little effect on improving the strength and pore structure of the separator. Its tensile strength is 4.0MPa and its compressive strength is 2.8MPa. It cannot effectively resist stress changes when the battery plate expands and contracts. It has low short-circuit resistance and is prone to cause internal short circuits in the battery, threatening battery safety.
[0070] 14-24°SR centrifugal cotton: 2% of the total fiber mass. Its toughness and adsorption properties have limited effect on improving the overall performance of the battery. The amount of electrolyte adsorbed is 6.5 times its own mass. It is difficult to ensure the durability of the battery and the stable supply of electrolyte under complex working conditions, resulting in large fluctuations in battery performance under different environmental conditions. In an environment with changing humidity (20%-80%), after 700 charge and discharge cycles, the battery capacity retention rate decreased by 25%.
[0071] Performance parameters: Porosity is 91%, and liquid absorption is 4.6g / m². The relatively low porosity and liquid absorption limit the distribution of electrolyte in the separator and the efficiency of ion transmission, causing the battery to lose a lot of energy during charging and discharging, which is manifested as reduced mileage, increased charging time, and shortened cycle life. In electric vehicle applications, the mileage is reduced by about 35% and the cycle life is shortened by about 40%; in the application of backup power supply for communication base stations, the power supply stability is insufficient and the long-term standby performance is significantly reduced.
[0072] Preparation method: Beating process: adjust the beating pH value to 3.5, weigh the fiber and slowly add it to the beater and add fumed silica (3.5% of the total fiber mass), and beat at 1500 rpm for 60 minutes. Although the fumed silica content is too high, it helps to disperse the fiber to a certain extent, and the average diameter of the fiber agglomerates is reduced from about 160 microns to about 60 microns, a decrease of 62.5%, but it will cause excessive coverage of the fiber surface, affect the interaction between the fibers, and lead to uneven structure after the separator is formed, and the porosity and liquid absorption rate are adversely affected, thereby reducing the battery performance.
[0073] Add water, mix and follow-up treatment: add 5 times the fiber mass of deionized water for 30 minutes of beating, then stir at 1000 rpm for 30 minutes, 5MPa pressure molding, 80℃ drying for 24 hours, cutting accuracy ±0.5mm and testing. The preparation process is similar to that of Example 1, but due to the unreasonable ratio of fiber raw materials and additives, the final separator performance is poor, and problems such as unstable performance and heating are prone to occur during the use of the battery, affecting the normal use and safety of the battery.
[0074] Application areas: In electric vehicle batteries, due to poor battery performance, the cruising range and cycle life cannot meet the use requirements, which will cause inconvenience to users and increase the cost of use. For example, an electric motorcycle using the comparative partition may need to be charged after traveling 50-80 kilometers, and the battery performance will drop significantly after about 1 year of use, while the partition of Example 1 can support 150-200 kilometers of cruising and stable performance for 3-5 years of use. In the backup power supply of communication base stations, the power supply reliability is low when the city power fails, which may cause communication equipment to fail due to power problems, affecting the quality of communication services and even causing communication interruptions. During a regional power grid failure, the backup power supply of the communication base station using the comparative partition may experience voltage drops, power outages and other problems, resulting in the interruption of communication services in the surrounding area for several hours, while the partition of Example 1 can provide stable power supply to ensure that communication services are not affected.
[0075] Comparative Example 3: Material composition: 25-30°SR glass fiber: 40% of the total fiber mass. The chemical stability is acceptable, and the structural integrity retention rate is 96% after 1000 hours of immersion test. However, due to the change in the proportion of other fibers, the overall synergy effect is not good. In the long-term operation of the battery, the protection and support of the separator structure is limited, and structural degradation is prone to occur. Its tensile strength is 3.2MPa. After withstanding 600 times of 20g acceleration impact, the deformation of the separator structure is about 8%.
[0076] 30-35°SR glass fiber: 30% of the total fiber mass. Compared with 25-30°SR glass fiber, the pore structure is relatively simple, with a porosity of 42% and a pore size distribution of 5-30 microns. The electrolyte storage and ion conductivity performance is average. During the battery charging and discharging process, it cannot provide an efficient transmission channel for ions, resulting in a slow battery charging and discharging speed and low energy conversion efficiency. In the battery charge and discharge cycle test, the electrolyte infiltration time was extended by 35% and the ion transmission resistance increased by 45%.
[0077] Bicomponent organic fiber: accounts for 25% of the total fiber mass, of which polyester fiber and polyacrylonitrile fiber each account for half. Although the content of bicomponent organic fiber is high, due to the imbalance of the overall fiber ratio, it is impossible to form an ideal interpenetrating network structure in the separator, and the mechanical properties and electrolyte adsorption and distribution properties cannot be fully exerted. The tensile strength of polyester fiber is 3.8MPa, the elongation at break is 24%, and the electrolyte adsorption rate of polyacrylonitrile fiber is 93%, which makes the separator prone to local deformation or uneven electrolyte distribution during battery use, affecting the stability of battery performance, and the voltage fluctuation range is about ±6%.
[0078] 40-45°SR glass fiber: 3% of the total fiber mass. The content is low, and the optimization effect on the strength and pore structure of the separator is not obvious. The tensile strength is 4.2MPa and the compressive strength is 3.0MPa. It is difficult to effectively buffer the stress changes of the battery plate, and the short-circuit resistance is weak, which increases the risk of internal short circuit of the battery and is not conducive to the safe and stable operation of the battery.
[0079] 14-24°SR centrifugal cotton: 2% of the total fiber mass. Its toughness and adsorption properties have limited impact on the overall performance of the battery. The amount of electrolyte adsorbed is 6.8 times its own mass. It is difficult to ensure the durability of the battery and the continuous supply of electrolyte under complex working conditions, causing the battery performance to fluctuate greatly under different environmental conditions and reduce reliability. In the temperature cycle (-8℃-58℃) test, after 800 cycles, the battery capacity retention rate decreased by 22%.
[0080] Performance parameters: Porosity is 91.5%, and liquid absorption rate is 4.7g / m². These performance parameters are relatively poor compared to Example 1, which limits the effective role of electrolyte and ions in the battery during charging and discharging, resulting in a decrease in the overall performance of the battery. In electric vehicle applications, the range is reduced, and in communication base station backup power applications, the power supply stability is insufficient. In electric vehicle applications, the range is reduced by about 32%. In communication base station backup power applications, the power supply stability is poor when the mains fails, and the performance of the long-term backup partition decreases rapidly.
[0081] Preparation method: Beating process: adjust the pH value of the beating environment to 3.5, take the fibers in proportion and slowly add them to the beater without adding fumed silica. Due to the lack of fumed silica, the fibers are difficult to disperse during the beating process and are prone to agglomeration. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates was reduced from about 200 microns to only about 180 microns, a decrease of 10%; the standard deviation of the fiber distribution per unit area was almost unchanged from about 45, and the uniformity was improved by about 2%. This results in uneven separator structure, poor mechanical properties, uneven adsorption and distribution of the electrolyte, and seriously affects the charge and discharge performance and cycle life of the battery.
[0082] Add water, mix and subsequent treatment: add 5 times the mass of fiber deionized water when beating for 30 minutes, then stir at 1000 rpm for 30 minutes, press 5MPa to form, dry at 80℃ for 24 hours, cut with an accuracy of ±0.5mm and test. Although the steps of adding water, mixing and subsequent treatment are the same as those in Example 1, because fumed silica is not added during the fiber beating process, the final separator performance is far inferior to that in Example 1, and various performance problems are likely to occur in the battery, such as increased internal resistance and reduced charge and discharge efficiency.
[0083] Application areas: When used in electric vehicle batteries and communication base station backup power supplies, in electric vehicles, battery performance declines significantly under long-term use and complex working conditions, the cruising range is reduced, the cycle life is shortened, and the user experience is poor. For example, when electric vehicles use the comparative partition, the acceleration performance declines, the charging time is prolonged, and the battery capacity decays severely after 2-3 years of use, while the partition of Example 1 can maintain good acceleration performance and charging efficiency, and the capacity decay is small after 3-5 years of use. In the backup power supply of communication base stations, the power supply stability is poor when the mains fails, and the performance of long-term backup partitions declines rapidly, which may cause power supply failures in communication base stations during mains interruptions, affecting the normal operation of the communication network. During long-term mains failures, the comparative partition may not be able to provide stable power supply, causing some equipment of the communication base station to shut down, affecting the continuity and stability of communication services, while the partition of Example 1 can ensure the normal operation of the communication base station.
[0084] Comparative Example 4: Material composition: 25-30°SR glass fiber: 45% of the total fiber mass. Good chemical stability, with a structural integrity retention rate of 97.5% after 1100 hours of immersion test. However, due to the unreasonable combination of other fiber components and proportions, its advantages are difficult to fully exert, and during battery operation, its role in improving the overall performance of the separator is limited. Its tensile strength is 3.6MPa, and after 700 times of 22g acceleration impact, the separator structure deformation is about 7%.
[0085] 30-35°SR glass fiber: 35% of the total fiber mass. The pore structure formed by combining with 25-30°SR glass fiber has a certain effect, with a porosity of 46.5% and a pore size distribution of 1.5-38 microns. However, due to the influence of subsequent processing factors, it cannot reach the optimal state, which has a certain impact on electrolyte storage and ion conduction efficiency. In the battery charge and discharge cycle test, the electrolyte infiltration time is extended by 25%, and the ion transmission resistance is increased by 35%.
[0086] Bicomponent organic fiber: accounts for 10% of the total fiber mass, of which polyester fiber accounts for 60% and polyacrylonitrile fiber accounts for 40%. The relatively large amount of polyester fiber ensures the mechanical properties of the separator to a certain extent, with a tensile strength of 4.0MPa and an elongation at break of 23%. However, the small amount of polyacrylonitrile fiber leads to insufficient uniformity of electrolyte adsorption and distribution, and affects the stability of ion transmission. The battery voltage fluctuates greatly during charging and discharging, and the voltage fluctuation range is about ±7%.
[0087] 40-45°SR glass fiber: accounts for 7% of the total fiber mass. Its inherent strength and ability to optimize the pore structure cannot be fully reflected due to other problems in the preparation process. Its tensile strength is 4.6MPa and its compressive strength is 3.3MPa. It has poor buffering effect when the battery plate expands and contracts, and its short-circuit resistance needs to be improved, which increases the risk of internal short circuits in the battery.
[0088] 14-24°SR centrifugal cotton: 3% of the total fiber mass. Its toughness and adsorption performance are difficult to play the maximum role in the overall uncoordinated fiber combination. The amount of electrolyte adsorbed is 7.3 times its own mass. It performs generally in terms of ensuring battery durability and electrolyte supply. In complex working conditions or long-term use, the battery performance declines rapidly. In the comprehensive environmental test of humidity and temperature changes (humidity 30%-90%, temperature -5℃-60℃), after 900 charge and discharge cycles, the battery capacity retention rate decreased by 20%.
[0089] Performance parameters: Porosity is 92%, and liquid absorption rate is 4.8g / m². Compared with Example 1, the performance parameters are at a disadvantage, which makes the electrolyte storage and ion transmission effects of the battery unsatisfactory during the charging and discharging process, resulting in a decrease in the overall performance of the battery, a decrease in the cruising range in electric vehicle applications, and a shortened cycle life; in the application of backup power supply for communication base stations, the power supply stability is insufficient, and the long-term standby performance is significantly reduced. In the application of electric vehicles, the cruising range is reduced by about 26%, and the cycle life is shortened by about 30%; in the application of backup power supply for communication base stations, the power supply stability is poor when the mains fails, and the performance of the partition decays rapidly during long-term standby.
[0090] Preparation method: Beating process: The pH value of the beating environment is adjusted to 4.5. Compared with the pH value of 3.5 in Example 1, this pH value is not conducive to the optimization of the fiber surface and the interaction between fibers. The degree of fiber hydrolysis reaction is different, resulting in poor fiber dispersion effect. The uniformity of the formed fiber dispersion system is not good, which affects the structure and performance of the partition. The fibers are weighed in proportion and slowly added to the beater. During the beating process, fumed silica is added at 2% of the total fiber mass. Although the content of fumed silica is the same as in Example 1, due to the inappropriate pH value, its effect on the fiber cannot be fully exerted, and the performance of the partition cannot be effectively improved. When stirred at a high speed of 1500 rpm, the average diameter of the fiber agglomerates decreased from about 135 microns to about 75 microns, a decrease of 44.4%; the standard deviation of fiber distribution per unit area decreased from about 33 to 26, and the uniformity increased by about 21.2%, both lower than Example 1. Beat at a speed of 1500 rpm for 60 minutes.
[0091] Add water for mixing and subsequent treatment: add 5 times the fiber mass of deionized water during beating for 30 minutes, then stir at 1000 rpm for 30 minutes, pour into a mold and form under 5MPa pressure, dry at 80℃ for 24 hours, cut with an accuracy of ±0.5mm and test. Due to the pH value problem during the beating process, even if the subsequent steps are the same, the final separator performance is still not as good as Example 1, and it shows poor stability and reliability in battery applications.
[0092] Application areas: Applied to electric vehicle batteries and communication base station backup power supplies. In electric vehicles, the battery performance fluctuates greatly under complex working conditions, the cruising range is significantly reduced, the cycle life is short, and more frequent maintenance and replacement of batteries are required. For example, in the operation of urban public buses, the battery pack using the four-partition plate of the comparative example may need to be inspected for deep maintenance every 3-4 months of operation, and the battery's cruising range will be reduced by about 30% when the vehicle is fully loaded, while the battery pack corresponding to the first embodiment can maintain a stable operation cycle of 6-8 months, and the cruising range is reduced by less than 10%. In the backup power supply of communication base stations, the power supply is unstable when the city power fails, and the performance of the partition decays rapidly during the long-term standby process, which may cause abnormal operation of the communication base station equipment and affect the continuity and stability of communication services. For example, when encountering a long-term regional power outage, the backup power supply of the communication base station using the four-partition plate of the comparative example may have problems such as unstable power supply voltage and current fluctuations after 2-3 days of power outage, affecting the normal operation of the base station equipment, while the partition of the first embodiment can provide stable power supply during a power outage for a week or even longer, ensuring the normal operation of the communication base station equipment.
[0093] After detailed analysis and testing of the AGM separators of Example 1, Example 2 to Example 4 and various comparative examples, in order to more intuitively present the performance differences between them, the key data are organized into the following table: project Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 25 - 30°SR glass fiber ratio (%) 45 42 48 40 / 55 40 45 30 - 35°SR glass fiber ratio (%) 35 38 32 40 / 25 30 35 Bicomponent organic fiber proportion (%) 10 13 10 13 / 15 25 10 40 - 45°SR glass fiber ratio (%) 7 6 8 5 / 3 3 7 14 - 24°SR centrifugal cotton ratio (%) 3 1 2 2 / 2 2 3 Porosity (%) 93 92 92.5 92 Not mentioned (lower than Example 1) 91 91.5 92 Liquid absorption rate (g / m²) 5.0 4.9 4.85 4.82 Not mentioned (lower than Example 1) 4.6 4.7 4.8 Ion migration rate (compared with Example 1) / 18% reduction / 20% reduction 35% reduction / / 20% lower than Example 1 Reduction in driving range (electric vehicle applications, %) / About 25% About 30% About 28% More than 40% About 35% About 32% About 26% Cycle life (in specific scenarios, times) 600-800 400-450 / / 300-400 / / / Improvement in battery charging and discharging efficiency (compared with ordinary separators) / / / / / / / / Electrolyte immersion time (compared with Example 1) / 20% longer 25% longer 18% longer 30% longer (estimated) 40% longer 35% longer 25% longer Ion transmission resistance (compared with Example 1) / 30% increase / 28% increase Increase by 40% (estimated) Increase by 50% 45% increase Increase by 35% Structural integrity retention rate (long-term immersion test, %) 98.5 95 99 97 90 / / / Tensile strength (MPa) / / / / / / / / Compressive strength (MPa) / / / / / / / / Performance in simulated battery transportation collision and use vibration tests No cracking or deformation after 120 times of 22g acceleration impact No cracking or deformation after 100 times of 20g acceleration impact / / / / There may be a risk of local deformation or cracking after 100 times of 20g acceleration shock / Performance in the battery positive and negative plate expansion and contraction simulation test After enduring 120 times of 6% volume change stress, the partition has no crack or deformation After enduring 100 times of 5% volume change stress, the partition structure deformation reached 8% / After enduring 110 times of 4% volume change stress, the partition structure deformation reached 10% / After enduring 100 times of 5% volume change stress, the probability of the partition rupture is 10% / After enduring 110 times of 4% volume change stress, the partition structure deformation reached 10% Power supply stability during mains failure (application of backup power supply for communication base stations) Stable power supply to ensure normal operation of communication base stations The power supply stability is slightly poor when the mains fails, and the performance degradation rate of the long-term standby partition is relatively high The power supply stability and long-term standby performance degradation ratio are not as ideal as in Example 1. The power supply stability is poor when the mains fails, and the performance of the long-term standby partition decreases rapidly Unstable power supply, unable to provide reliable power supply for a long time Low power supply reliability may cause communication equipment failure The power supply stability is poor when the mains fails, and the performance of the long-term standby partition decreases rapidly The power supply is unstable when the mains fails, and the performance of the partition deteriorates quickly during long-term standby. In summary, embodiment 1 is the best embodiment.
[0094] Summarize: 1. Improved chemical stability: Example 1 uses a specific proportion (45%) of 25-30° SR glass fiber. Its excellent chemical stability enables the separator to maintain structural integrity for a long time in the complex and highly corrosive electrolyte environment of the lead-acid battery, effectively preventing the separator from being corroded, greatly extending the service life of the separator, and providing reliable protection for the long-term stable operation of the battery. In contrast, due to material and structural limitations, traditional AGM separators have limited ability to resist electrolyte corrosion and poor long-term stability, which can easily lead to damage to the separator structure, thereby affecting the normal operation and life of the battery. The high-performance separator significantly overcomes this problem, reduces the risk of battery performance degradation and failure due to corrosion, and improves the overall durability and reliability of the battery. In the long-term immersion test, the partition structure integrity retention rate of Example 1 is as high as 98.5%, while that of Comparative Example 1 is only 90%. Under the influence of factors such as the close arrangement of fibers and the limited pore structure, although the chemical stability of Comparative Example 2 has certain performance, the overall corrosion resistance is still inferior to that of Example 1. In actual battery operation, the performance of Comparative Example 1 may be significantly reduced due to corrosion after 1-2 years of use, while Example 1 can maintain stable operation for 3-5 years.
[0095] 2. Enhanced mechanical properties: Structural stability: Example 1 uses a reasonable combination of multiple fibers, such as 50% polyester fiber and 50% polyacrylonitrile fiber in the two-component organic fiber, and the two work together to form an interpenetrating network structure, giving the separator excellent mechanical properties. Polyester fiber contributes high strength and excellent toughness to the separator by virtue of its unique molecular structure, and can effectively disperse and absorb the external stress generated by the battery during transportation and use due to bumps, collisions, frequent starts and stops, or driving on rough roads, etc., to prevent the separator from being damaged by rupture, deformation, etc., and effectively guarantees the integrity and stability of the internal structure of the battery, ensuring that the battery can continue to operate normally. It effectively solves the shortcomings of traditional AGM separators in mechanical properties, avoids faults such as internal short circuits of batteries caused by damage to the separator, and improves the safety of battery use. For example, in the simulated battery transportation collision and use vibration test, the separator of Example 1 did not rupture or deform after 120 times of 22g acceleration impact, while the mechanical properties of Comparative Example 3 could not be fully exerted due to the imbalance of fiber ratio, and there may be a risk of local deformation or rupture after 100 times of 20g acceleration impact.
[0096] Anti-plate stress ability: 40-45°SR glass fiber accounts for 7% of the total fiber mass. Its high strength and good flexibility are perfectly combined, and it is woven into a fine and stable fiber network inside the separator. During the battery charging and discharging process, when the positive and negative plates expand and contract, the fiber network can effectively buffer and disperse stress changes with its excellent elasticity and toughness, preventing the separator from breaking and deforming due to the inability to withstand stress, further ensuring that the normal operation of the battery is not affected, maintaining the stability of the internal structure of the battery, and reducing the damage to the separator and battery performance degradation caused by the plate stress. In the simulation test of the expansion and contraction of the positive and negative plates of the battery, the separator of Example 1 did not break or deform after being subjected to 120 times of 6% volume change stress, while the comparative example 2 had a 10% probability of breaking the separator after being subjected to 100 times of 5% volume change stress due to insufficient 40-45°SR glass fiber content. The comparative example 4 had a pH value problem during the preparation process that affected the performance of the glass fiber. After being subjected to 110 times of 4% volume change stress, the deformation of the separator structure reached 10%, which was far less than that of Example 1.
[0097] 3. Pore structure optimization: Electrolyte storage and ion transmission: Example 1: By interweaving 25-30°SR glass fiber (45%) and 30-35°SR glass fiber (35%), a diversified pore structure is constructed to provide sufficient and suitable storage space for the electrolyte, ensuring that the electrolyte can fully infiltrate every corner of the separator during the entire cycle of battery charge and discharge, so that ion transmission always has a stable and good medium environment. At the same time, this diversified pore structure significantly reduces the resistance of ion transmission in the separator, greatly improves the battery's charge and discharge efficiency, enables the battery to complete the charging process in a shorter time, and can release stronger and more lasting electrical energy during discharge. However, the pore structure of the traditional AGM separator is not ideal, the electrolyte storage space is limited, and the ion conduction channel is not smooth enough, resulting in uneven electrolyte distribution, low ion transmission efficiency, and limiting the battery's charge and discharge efficiency. This high-performance separator effectively improves this situation, meets the requirements of modern high-performance batteries for fast charging and discharging, and improves the battery's power performance and use efficiency. In the battery charge and discharge cycle test, the electrolyte infiltration time of Example 1 is shortened by 35%, and the ion transmission resistance is reduced by 42%. However, due to the single and imperfect pore structure of Comparative Example 1, the electrolyte infiltration time is extended by 30%, and the ion transmission resistance is increased by 40%. Due to the simple pore structure of Comparative Example 3, the electrolyte infiltration time is extended by 35%, and the ion transmission resistance is increased by 45%, which are both significantly different from Example 1.
[0098] Blocking the migration of active substances: 40-45°SR glass fiber can also finely optimize the pore structure of the separator, making the pore distribution more uniform and dense, which is not only conducive to the rapid penetration and uniform diffusion of the electrolyte in the separator, creating more favorable conditions for ion transmission, but also can effectively block the migration of active substances in the positive and negative plates, reducing the risk of internal short circuits in the battery, just like setting up a safety barrier for the battery, further improving the safety and stability of the battery, and reducing the battery performance degradation and failure probability caused by the migration of active substances. In the test of the migration of active substances in the positive and negative plates, the mobility of Example 1 was reduced by 85%, while the mobility of Comparative Example 2 was reduced by only 75% due to the insufficient content of 40-45°SR glass fiber, and the mobility reduction effect of Comparative Example 4 was not ideal due to the poor fiber synergy effect, which increased the risk of internal short circuits in the battery.
[0099] 4. Excellent application performance: Electric vehicle battery application: In electric vehicle batteries, the high-performance AGM separator of Example 1 can ensure a stable supply of electrolyte and smooth transmission of ions under frequent charging and discharging and complex vibration environments due to its high porosity (93%), high liquid absorption rate (5.0g / m²) and excellent mechanical properties, effectively extending the cycle life of the battery and reducing the attenuation of the driving range. For example, in the daily use of electric vehicles, whether it is frequent starting and stopping on urban roads or long-term driving on highways, the AGM separator can ensure the stability of battery performance and improve the efficiency and economy of electric vehicles. Compared with traditional AGM separators, it solves the problem of reduced battery life due to poor separator performance, improves the overall performance and user experience of electric vehicles, and reduces the cost of use, such as reducing the need for more frequent battery replacement due to battery performance attenuation. In actual applications, the battery cycle life of Example 1 is extended by 32% compared with the ordinary partition, and the cruising range attenuation rate is reduced by 22%. However, the cruising range of Example 1 is seriously insufficient, the cycle life is short, and the battery needs to be replaced frequently. The cruising range of Example 3 is reduced by about 32%, and the cycle life is shortened, and both cannot meet the high performance requirements of electric vehicles.
[0100] Communication base station backup power supply application: In the communication base station backup power supply, the high stability and long cycle life of the AGM separator of Example 1 can ensure that when the mains fails, the battery can quickly and stably power the communication equipment, and the performance degradation is minimal during the long-term standby process. Even in the case of large changes in ambient temperature, it can rely on its good performance, especially the synergistic effect of the two-component organic fiber, to ensure the normal operation of the battery, provide strong support for the stable operation of the communication base station, and reduce the risk of communication failures caused by power problems. In the application of communication base station backup power supplies, traditional AGM separators often have performance defects, such as unstable power supply when the mains fails, and rapid performance degradation of long-term standby separators, which affect the quality and continuity of communication services. The high-performance separator effectively overcomes these problems, improves the reliability and stability of the communication base station backup power supply, ensures the normal operation of the communication network, reduces communication interruptions and service quality degradation caused by power failures, and has important social and economic value. In the application of backup power supply for communication base stations, the power supply response time of embodiment 1 is shortened by 18% when the mains power fails, the performance degradation rate of long-term standby (one year) is controlled within 4%, and the battery working stability is improved by 32% when the ambient temperature changes (-18℃-55℃). However, in comparison example 1, the power supply is unstable when the mains power fails, and it cannot be reliably supplied for a long time. In comparison example 2, the power supply reliability is low when the mains power fails, which may cause communication equipment failure. In comparison example 4, the power supply is unstable when the mains power fails, and the performance of the partition decays rapidly during long-term standby, which makes it difficult to ensure the stable operation of the communication base station.
[0101] In summary, the high-performance lead-acid battery AGM separator exhibits excellent characteristics in terms of material composition, preparation method, and application performance, comprehensively solves the problems existing in traditional AGM separators, significantly improves the performance, stability, and durability of batteries under complex working conditions, and meets the urgent needs of practical application scenarios such as electric vehicles and communication base station backup power supplies for high-performance batteries, which has a positive role in promoting the development of the lead-acid battery field. Through a detailed comparative analysis of the embodiments and the comparative examples, the advantages of the first embodiment in various aspects and its key role in improving the overall performance of the battery are more clearly demonstrated, providing a strong reference for further research, production, and application of high-performance lead-acid battery AGM separators.
Claims
1. A high performance lead-acid battery AGM separator, characterized in that: It is composed of 25-30°SR glass fiber, 30-35°SR glass fiber and two-component organic fiber, 40-45°SR glass fiber, 14-24°SR centrifugal cotton and additive fumed silica; Among them, 25-30°SR glass fiber accounts for 40%-50% of the total fiber mass, 30-35°SR glass fiber accounts for 30%-40% of the total fiber mass, 40-45°SR glass fiber accounts for 5%-10% of the total fiber mass, 14-24°SR centrifugal cotton accounts for 3%-8% of the total fiber mass, additives such as fumed silica account for 1%-3% of the total fiber mass, and bicomponent organic fiber accounts for 3%-18% of the total fiber mass. Bicomponent organic fiber is a combination of polyester fiber and polyacrylonitrile fiber.
2. A high performance lead-acid battery AGM separator as claimed in claim 1, characterized in that: The 30-35° SR glass fiber cooperates with the 25-30° SR glass fiber to form a pore structure.
3. A high performance lead-acid battery AGM separator as claimed in claim 1, characterized in that: The synergistic effect of the polyester fiber and the polyacrylonitrile fiber group forms an interpenetrating network structure.
4. A method for preparing a high-performance lead-acid battery AGM separator, based on a high-performance lead-acid battery AGM separator according to any one of claims 1 to 3, characterized in that: The following steps are involved: Beating process: Use a beater and add sulfuric acid solution to adjust the pH value; Weigh glass fiber and two-component organic fiber in proportion, slowly add them into a pulping machine, add additives during the pulping process, the additives added include but are not limited to fumed silica, and beat at a speed of 1500 rpm for 60 minutes; Add water for mixing and subsequent treatment: After 30 minutes of beating, slowly add deionized water. After adding water, stir for 30 minutes; pour the fiber slurry into a special mold, apply 5MPa pressure to form it, and dry it at 80℃ for 24 hours; cut the dried AGM partition with a cutting accuracy of ±0.5mm, and conduct appearance inspection and physical property test.
5. The method for preparing a high performance lead-acid battery AGM separator according to claim 4, characterized in that: The pH value of the pulping environment during the pulping process is controlled at 3.
5.
6. The method for preparing a high performance lead-acid battery AGM separator according to claim 4, characterized in that: In the process of adding water and mixing in the subsequent treatment, the deionized water is 5 times the total fiber mass, and then stirred at 1000 rpm.
7. The method for preparing a high performance lead-acid battery AGM separator according to claim 4, characterized in that: The porosity of the obtained AGM separator is not less than 92%, and the liquid absorption rate is not less than 4.8g / m².
8. An application of a high-performance lead-acid battery AGM separator, based on the preparation method of a high-performance lead-acid battery AGM separator according to any one of claims 5 to 7, characterized in that: Separators are used in electric vehicle batteries and communication base station backup power supplies.
Citation Information
Patent Citations
Hybrid glass fiber diaphragm for storage battery as well as method and system for manufacturing hybrid glass fiber diaphragm
CN102496689A
Lead storage battery
CN103262299A
Preparation method of high-dendritic-crystal-resistance short circuit baffle plate
CN103400950A
AGM separator with stable elasticity and production method thereof
CN108598346A
Separator for valve-regulated lead acid battery using glass fiber and heat-fusible organic fiber
US20230078669A1